Sex Moderates Reward- and Loss-Related Neural Correlates of Triarchic-Model Traits and Antisocial Behavior. (July 2022) - Brislin, Sarah J.; Weigard, Alexander S.; Hardee, Jillian E.; Cope, Lora M.; Martz, Meghan E.; Zucker, Robert A.; Heitzeg, Mary M.
Abnormalities in responses to reward and loss are implicated in the etiology of antisocial behavior and psychopathic traits. Although there is evidence for sex differences in neural response to reward and loss, it remains unclear how sex differences may moderate links between these neural responses and the phenotypic expression of antisocial behavior and psychopathic traits. This study examined sex differences in associations of neural response to reward and loss with antisocial personality symptoms and psychopathic traits. Functional neuroimaging data were collected during a monetary incentive delay task from 158 participants. Among males, during loss anticipation, activation in the left nucleus accumbens was negatively associated with antisocial behavior. Among females, during loss feedback, activation in the left nucleus accumbens and left amygdala was negatively associated with antisocial behavior. These results suggest that phenotypic sex differences in psychopathic traits and antisocial behavior may in part be attributable to different etiological pathways.